N & O : Enne & Zero - Enne & Zero - Enne & Zero : Motus etc. - Museion - Museo d'Arte Moderna, Bolzano; Palazzo della Ragione, Padova; Galleria d'Arte Moderna e Contemporanea, San Marino; Argan, Giulio Carlo; Fantelli, Pier Luigi; Hapkemeyer, Andreas; Menicucci, Pier Marino; Michelotti, Francesca; Nicolussi-Leck, Karl; Schmied, Wieland; Segato, Giorgio; Siena, Pier Luigi; et al. (Wien : Folio Verlag, 1996)
Adrian, Marc ; Alviani, Getulio ; Biasi, Alberto ; Bury, Pol ; Calder, Alexander ; Castellani, Enrico ; Chiggio, Ennio ; Colombo, Gianni ; Costa, Toni ; Cruz-Diez, Carlos ; Dorazio, Piero ; Durante, Armando ; Franchina, Nino ; Holweck, Oskar ; Klein, Yves ; Kounellis, Jannis ; Landi, Edoardo ; Parc, Julio Le ; Luther, Adolf ; Mack, Heinz ; Manzoni, Piero ; Massironi, Manfredo ; Megert, Christian ; Morellet, François ; Munari, Bruno ; Perilli, Achille ; Piene, Otto ; Soto, Jesus Rafael ; Tancredi ; Tinguely, Jean ; Uecker, Günther ; Varisco, Grazia ; Vasarely, Victor ; Vassilakis, Takis
biografie
N & O : Enne & Zero - Enne & Zero - Enne & Zero : Motus etc., Museion - Museo d'Arte Moderna, Bolzano, 1.3. 19.5.1996 / Palazzo della Ragione, Padova, 1.6. - 18.8.1996 / Galleria d'Arte Moderna e Contemporanea, San Marino, 30.8. - 6.10.1996
Duits
Duits & Italiaans
Italiaans
boek